PENGARUH PENGGUNAAN TIPE COOPERATIVE SCRIPT TERHADAP KETERAMPILAN BERBICARA DI SEKOLAH DASAR - Arfianti, Desi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aimed to analyze the influence of media use Cooperative Script tipe in Indonesian language learning the speaking skills of the three grade students of SD Negeri 01 Rasau Jaya. This study used an experimental method to form quasy Experimental kind Nonequivalent Control Group Design. The population in this research were 48 students in which the entire population sampled. Samples were class III A as the experiment class and III class B as a class control. Data collector in the form of oral tests were 3 questions. The calculation result obtained t test (2,98)> t table (1.6658) with significance level Î± = 5% means a significant influence on Cooperative Script tipe. From the calculation of effect size (ES) of 0.95 with the criteria of high. This means that Cooperative Script tipe give high effect learning the Indonesian language on speaking skills of the three grade students of SD Negeri 01 Rasau Jaya. Keywords: Influence, Cooperative Script Tipe, Speaking Skills